Factors affecting N2O fluxes from heavy metal-contaminated mangrove soils in a subtropical estuary. (January 2023) - Ma, Jiaojiao; Niu, Anyi; Liao, Zhenni; Qin, Junhao; Xu, Songjun; Lin, Chuxia
Abstract: A 1-year field monitoring program was carried out to observe seasonal variation in N2 O fluxes at two typical mangrove wetlands in a subtropical estuary. The soils in the island-type mangrove wetland had a higher level of heavy metal(loid) contamination and a lower level of salinity compared to the small bay-type mangrove wetland. While there was a high level of similarity in the seasonal variation pattern of N2 O fluxes between the two investigated sites with both being significantly higher in summer than in other seasons, the average of N2 O fluxes in the island-type mangrove wetland was 7.19 μg·m −2 ·h −1 ， which tended to be lower compared to the small bay-type mangrove wetland (15.63 μg·m −2 ·h −1 ). Overall, N2 O flux was closely related to soil-borne heavy metal(loid)s, showing a trend to decrease with increasing concentration of these heavy metal(loid)s. The N2 O fluxes increased with decreasing abundance of either denitrifiers or nitrifiers. But the opposite was observed for the anammox bacteria present in the soils. The anammox bacteria were more sensitive to heavy metal(loid) stress but more tolerated high salinity encountered in the investigated soils compared to the denitrifiers or nitrifiers. It appears that anammox reactions mediated by anammox bacteria played a key role in affecting the spatial variation in N2 O fluxes from the mangrove soils in the study area. And an increased level of ammonium in soils tended to promote the activity of anammox bacteria and consequently enhanced N2 O emission from the mangrove soils. Highlights: N2 O flux monitoring in two different types of mangrove wetlands was conducted. N2 O fluxes from the soils varied seasonally with peaks occurring in the summer. N2 O emission decreased with increasing level of heavy metal(loid) contamination. Anammox bacteria not nitrifiers/denitrifiers were inhibited by heavy metal(loid)s. Anammox reaction played a key role in shaping the spatial variation in N2 O fluxes.